Growth of Exclusively and Non-Exclusively Breast Fed Infants (0-4 Months) in Posyandu Kenangan Area, District of Deli Serdang - Riza I. Nasution; Fauzah Fauzah; Endang S. Hamid; S.M. Manoeroeng (Indonesian Pediatric Society, 1997)
A prospective study of all infants visited Posyandu in Kenangan Area was done to study their growth until the age of 4 months according to their feeding pattern (exclusively breast fed or not) This study lasted for 3 months (December 1992 until February 1993). Ninety two infants met the study criteria (spontaneous delivery and cry immediately, no congenital anomaly, body weight over 2500 gram, and appropriate for gestational age). In most of these infants, the first visit was at 1-2 months age (34 infants or 36%). The number of infants with exclusively breast fed was 25 or 26% and non-exclusively breast fed was 67 or 74%. There were 38 infants or 41% who got breast feeding exclusively since bulb and 48 or 51% after 25-72 hours following birth. There were 50 infants or 52% who got supplementary food before 2 month age. The average monthly body weight increase, in exclusively breast fed group was higher than in non-exclusively breast fed group infants.